Design of Restobarge Garbage and Sanitary Systems - Hari Prastowo; Agoes Santoso; Muhammad Badrus Zaman; Rizqi Ramadhan (International Journal of Marine Engineering Innovation and Research, 2019)
resto-barge is a barge which converted to floating restaurant, as an answer lacking orders of barge recently. The location is taking in Gili Trawangan, Lombok. The purpose is to design and calculate sewage, sanitary and garbage management systems. Also to calculate bill of material. The sanitary systems have a Taiko UH-2.0 Hydrophore pressure tank. The sewage systems have an Ebara 60 m3/h with meter head 15 m. Total cost spent to build those systems is IDR 115.244.500.